English in tourism : student's book - Jakubowski, Mariusz (Akademia Wychowania Fizycznego im. Bronisława Czecha (Kraków), 1999)
Spis treści: - s. 1;. Beginning and introduction to tourism – s. 9; 2. Antiquity – s. 18; 3. The crusades. - s. 25; 4. Medieval pilgrimages – s. 36; 5. The grand tour – s. 43; 6. Romanticism and tourism – s. 52; 7. Thomas cook. - s. 60; 8. Modern tourism – s. 70; 9. Tourism - a sociological phenomenon. - s. 78; 10. Tourism - an anthropological phenomenon - s. 87; 11. Goals of tourism: culture and nature. - s. 97; 12. The environmental effects of tourism – s. 111; 13. Commercialisationof tourism – s. 118; 14. Modern tourism- a passport to prosperity? - s. 129; 15. Mass tourism and its side effects – s. 135; 16. What is modern tourism sensitive to? - s. 145; 17. Hotel lobbying groups in tourism. - s. 153; 18. Anapocalyptic scen ario for the future of tourism. - s. 166; 19. Green and gentle tourism. - s. 174; 20. Special interest holidays (theme holidays) – s. 181; 21. Can modern mass tourism be controlled? - s. 191
Kopia cyfrowa, oryginał: Kraków : Akademia Wychowania Fizycznego im. Bronisława Czecha, 1999
Keywords: JĘZYK ANGIELSKI; PODRĘCZNIK AKADEMICKI